Prosthetic Rehabilitation: The Impact of Awareness, Attitude, and Behavior on Treatment Decision-Making: Insights from Bahria University Dental Hospital - Baqar , Anum; Hakeem , Saman; Ilyas , Farnaz; Monpuri , Asim; Abbas , Akbar; Mehwish , Ayesha; Javaid , Farah; Mazhar , Saima; Rameez , Mohammad (Research Highlights in Disease and Health Research Vol. 8, 2023)
This chapter presents the results of a study that was conducted at the Bahria University Dental Hospital in Karachi. The study aimed to assess the awareness, attitudes, and behavior trends of partially edentulous patients towards rehabilitation for missing teeth. Data was collected through in-depth interviews using a self- designed 12-item close-ended questionnaire. The study sample comprised 580 patients, with a higher proportion of females (63.4%) than males (36.6%). The majority of patients (61.4%) had partial edentulism in both arches, and fixed partial denture (49%) was the prosthesis of choice mainly by females (51%). Financial issues (47.6%) were the major barrier accessing dental services. The study also revealed the role of education in improving one’s awareness, the importance of attitude and behavior in the context of oral health, and how individuals can get awareness and motivation towards prosthetic rehabilitation by friends and relatives. Additionally, the study highlights the role of health professionals in guiding patients towards the right direction and addressing their clinical needs.